Findings on agricultural cleaner production in the three Gorges Reservoir Area. Issue 3 (March 2023) - Zhou, Houzhen; Luo, Xiaolan; Wang, Shuai; Wang, Zhaoli; Chen, Yangwu; Li, Xin; Tan, Zhouliang
Abstract: The 'rural revitalization strategy' is important to achieve sustainable development in the Three Gorges Reservoir Area (TGRA), the largest reservoir in China, located in the poverty alleviation region of the Qinling-Daba mountains, and characterized as mountainous and hilly dominated by backwards resettlements. Pig farming around the reservoir area is a key industry, accounting for 0.90% of the arable land area in the country, while the annual pig market represents a 1.37% share of the national figure. Here, 12 study sites were investigated on-site for understanding agricultural green development in the TGRA. We found two main prevailing models: one of ecological circulation (EC), based on animal husbandry and recycling. Of the 12 site, six cases of the ecological circulation model relied on pig husbandry, combined with cropping (grains/fruits/vegetables) by eco-industrial chains, such as pig-biogas-fruit (grain/vegetables), to prevent environmental pollution, while promoting agricultural economic growth by recycling fecal residues and wastewater (FSW) from pig-husbandry facilities to the fields. Our analysis predicted that a farm holding 10, 000 pigs may save inorganic nitrogen and phosphorus fertilizers by as much as 74.36 and 11.15 ton·a −1, respectively. On the other hand, five cases of ecological models oriented towards agritourism provided tourists with high-quality ecological products while coordinating environment protection with economic development. In addition, 11 research points applied water and fertilizer integration system for the purpose of saving water. However, lack of sufficient supporting arable land made intensive pig farming a risk of ecological degradation. Green control technologies are rarely used leading to an increase in the type and amount of pesticides. Our study has theoretical and practical significance for decision-makers to promote agricultural cleaner production (ACP).